2016
DOI: 10.22159/ajpcr.2016.v9i6.13960
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Aqueous Garlic Extract on Beta-Lactamase Producing Acinetobacter Isolates From Skin and Soft Tissue Infections

Abstract: Objective: The present study evaluates the antibacterial effect of aqueous garlic extract (AGE) on beta-lactamase-producing Acinetobacter strains isolated from skin and soft tissue infections (SSTIs). Methods:A total of 41 non-duplicate strains of Acinetobacter isolated from SSTIs specimens were tested for their antibiotic susceptibility pattern by Kirby-Bauer disk diffusion method. Ceftazidime-resistant Acinetobacter strains were screened for beta-lactamase production by phenotypic confirmatory disc diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, a study by Guoliang et al (2015) reports a synergistic association between AGE and Cefotaxime against non-beta-lactamase producing Pseudomonas aeruginosa, Candida albicans, and Methicillinresistant Staphylococcus aureus. Previous study carried out by Shah et al (2016) also reported synergistic activity between Cefotaxime and AGE against Acinetobacter strains which coproduce ESBL and AmpC.…”
Section: Type Of Interaction Esbl+ Ampcmentioning
confidence: 66%
See 3 more Smart Citations
“…However, a study by Guoliang et al (2015) reports a synergistic association between AGE and Cefotaxime against non-beta-lactamase producing Pseudomonas aeruginosa, Candida albicans, and Methicillinresistant Staphylococcus aureus. Previous study carried out by Shah et al (2016) also reported synergistic activity between Cefotaxime and AGE against Acinetobacter strains which coproduce ESBL and AmpC.…”
Section: Type Of Interaction Esbl+ Ampcmentioning
confidence: 66%
“…E-test ESBL and AmpC detection Ezy MIC TM strip (EM081, HiMedia, Mumbai, India) along with pure ESBL detection strips (EM079 Hi-Media, Mumbai, India) were used in the study. The strains were confirmed as ESBL and AmpC beta-lactamase coproducer in reference with the application sheet provided by the manufacturer (CLSI, 2012;Shah et al, 2016). The confirmed ESBL and AmpC co-producers were considered as the test strains in the study.…”
Section: Phenotypic Confirmatory Disc Diffusion Test (Pcddt)mentioning
confidence: 99%
See 2 more Smart Citations